On the transgranular type of tempered martensite embrittlement - Lee, Kon Bae; Yoon, Sang Hoon; Kwon, Hoon (Scripta metallurgica et materialia, 1994)
A phenomenon where toughness and strength of martensitic alloy steels are reduced, when tempered at 250-400 deg C, is called tempered martensite embrittlement (TME). There are two types of TME based upon fracture mode. Transgranular type of TME has been analyzed for its impact toughness, fracture behavior and microstructures on isothermal tempering. Molybdenum and MoW steels were used for experimentation because they may decrease the intrinsic toughness and produce easy transgranular brittle fracture. Impact testing was carried out and transmission electron microscope was used for studying the specimens. Results obtained were discussed. Molybdenum and MoW steels represented the quasi-cleavage fracture. The formation of coarse carbides at martensite lath boundaries results in TME which makes easy transgranular brittle fracture in the matrix of low intrinsic toughness with the tungsten and/or Mo additions.